Pediatric autoimmune retinopathy and optic neuropathy: a case report and a review of the literature - Varma, Hersh; Zhang, Kevin X.; Shah, Veeral S. (Frontiers in Ophthalmology, 2023)
Purpose: To present a rare case of pediatric bilateral optic neuropathy and retinopathy consistent with a diagnosis of autoimmune retinopathy. We review the most current literature and phenotypes associated with reported pediatric cases of autoimmune retinopathy.Design: Case report with retrospective case series literature review Subjects: This study incorporated data from six subjects, with one presented as an original case report and five accessed from the English language literature to date.Methods: Descriptive analysis of fundus findings, electrophysiologic testing, serum autoantibody testing, OCT, brain MRI, and fluorescein angiography was performed where available.We evaluated the clinical presentation and treatment outcomes of all subjects and followed their visual function over time.Results: All six subjects had retinal abnormalities documented on imaging while five out of six had optic nerve abnormalities. Electrophysiologic testing was performed in three subjects, all which were abnormal. An underlying neoplastic disorder was described in four subjects. Serum autoantibody testing was available in four subjects, and included antibodies against: 22kDa antigen, 35kDa optic nerve-derived antigen, 62kDa antigen, enolase, recoverin, tubulin, and pyruvate kinase M2. Our subject presented 12 years after resection of ganglioglioma with asymmetric bilateral vision loss, disc edema in one eye, advanced disc pallor in the fellow eye, and bilateral subtle retinal infiltrates despite a normal fluorescein angiogram. OCT demonstrated asymmetric ganglion cell layer thinning consistent with the vision loss. Our subject also had abnormal brain MRI findings of widespread pachymeningeal enhancement, but normal cerebrospinal fluid composition. He was initially treated with high-dose pulse steroids, followed by intravenous immunoglobulin therapy. He experienced partial visual recovery in both eyes.Conclusions: Pediatric autoimmune retinopathy and optic neuropathy is a rare disease that can present with unique signs and symptoms. In pediatric patients who present with symptoms of subacute progressive vision loss with negative inflammatory workup, a history of prior neoplasm, and/or clinical findings of progressive retinopathy or optic neuropathy, an autoimmune process should be considered in the differential.